2009
DOI: 10.1097/tp.0b013e3181a1719b
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Dystrophy Therapy by Nonautologous Mesenchymal Stem Cells: Muscle Regeneration Without Immunosuppression and Inflammation

Abstract: Background The use of non-autologous stem cells isolated from healthy donors for stem cell therapy is an attractive approach since the stem cells can be culture expanded in advance, thoroughly tested, and formulated into off-the-shelf medicine. However, HLA compatibility and related immunosuppressive protocols can compromise therapeutic efficacy and cause unwanted side effects. Methods Mesenchymal stem cells (MSCs) have been postulated to possess unique immune regulatory function. We explored the immunomodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 41 publications
4
70
1
1
Order By: Relevance
“…Instead, it is believed that MSCs exert their therapeutic effects through secreted paracrine or trophic factors [15][16][17]. Experiments utilizing MSC-conditioned media have demonstrated the importance of the paracrine mechanism of BM-MSC-induced wound healing [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it is believed that MSCs exert their therapeutic effects through secreted paracrine or trophic factors [15][16][17]. Experiments utilizing MSC-conditioned media have demonstrated the importance of the paracrine mechanism of BM-MSC-induced wound healing [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Instead it is believed that MSCs exert their therapeutic effects by secreting soluble or ''paracrine'' factors that augment endogenous repair and regenerative mechanisms [15][16][17][18]. Also, work in our laboratory has found that MSCs can enhance fibroblast migration, an integral component of the wound healing process, without direct contact, suggesting the importance of paracrine signaling between these cells [19].…”
mentioning
confidence: 99%
“…For example, prenatal tolerance induction has been a main goal of in utero hematopoietic stem cell transplantation, to facilitate postnatal cellular transplantation [2,3]. Due to their recently described multilineage differentiation, and regenerative and immunomodulatory capabilities, mesenchymal stem cells (MSCs) are also being actively explored for the treatment of established nonhematopoietic diseases, including musculoskeletal defects [4][5][6][7], and to improve hematopoietic stem cell engraftment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, intracoronary infusion of MSCs for heart therapy, which retained only 1%-2% of the infused cells in the porcine myocardium, was found to result in significant functional improvement in the hibernating myocardium [112,113] . The recognition that IL-6 and IL-6-type cytokines are abundantly produced by MSCs [6,55] and that skeletal muscle actively induces IL-6 during exercise [56,114] prompted us to pioneer an intramuscular (im) MSC delivery route for cardiac repair [6,30,115] . This im MSC therapeutic strategy is coupled to the inherent ability of skeletal muscle to produce beneficial trophic factors in response to exercise and injury [116][117][118] , and therefore represents an integrative physiological approach.…”
Section: A Rational Design Of Msc Administration Routementioning
confidence: 99%